Neonatal care cost of “adverse neonatal outcome” following term deliveries in SriLanka - Gunawardane, Damitha Asanga; Dharmaratne, Samath D; Rowel, Dhammica S (Bangladesh Journal of Medical Science, 2023)
Objective: To analyse the neonatal care cost of ‘adverse neonatal outcome’ following term deliveries (37 completed weeks - 41 completed weeks and 6 days) at Teaching Hospital Kandy. Method: This study was conducted from the 26th of February to the 20th of May 2015. This is a cost analysis to explore the neonatal care cost of term neonates with ‘adverse neonatal outcome’. ‘Adverse neonatal outcome’ was defined as a composite measure of neonatal death and morbidity, which needed admission to a neonatal care unit or neonatal intensive care unit before the initial discharge point. The perspective taken was that of the Ministry of Health Sri Lanka (MOHSL). One hundred and seventy-five eligible term neonates with ‘adverse neonatal outcome’ were recruited for the study consecutively until the required sample size is fulfilled. Results: Out of all term neonates delivered during the study period, 15.84% (n=175/1105) were admitted to the Neonatal Care Unit (NCU). During the study period, the total neonatal care cost(for 175 term neonates) was LKR. 12,140,040 (USD 89305),of which 69.0% was due to staff salaries and allowances. The median total neonatal care cost per term neonates with ‘adverse neonatal outcome’ was LKR. 50,193 (USD369) with an interquartile range of LKR. 39,047 (USD 287) to LKR. 79,638 (USD 586) Respiratory distress syndrome was the condition that required the most significant proportion (25%) of total neonatal care cost of term neonates with ‘adverse neonatal outcome’. Birth asphyxia was the most costly neonatal condition to manage as per the neonate median neonatal care cost (LKR.71278, USD 524). Conclusion: Expenditure on the ‘adverse neonatal outcome’ of term neonates was considerable. Birth asphyxia was the most costly neonatal condition to manage as per the median neonatal care cost. So, it is essential to strengthening the preventive strategies to reduce the ‘adverse neonatal outcome’ among term neonates. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 316-322